ROPE TRUSS: An EFFECTIVE TOOL FOR MANAGEMENT OF EVERSION OF UTERUS IN BUFFALOES - PATIL, A D; RAZZAQUE, W A A; RAMTEKE, S S; YEWLE, L V (The Indian Journal of Animal Reproduction, 2021)
The present study describes successful management of post-partum eversion of uterus in six buffaloes presented to Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Udgir.